STUDENTS’ LIVED EXPERIENCE IN UTILIZING QUILLBOT AS AN ONLINE PARAPHRASING TOOL IN ACADEMIC WRITING - Yosephine Viadestyas Asmara; Fidelis Chosa Kastuhandani (Universitas Muhammadiyah Tangerang, 2024)
This study aimed to investigate students’ lived experience of Quillbot utilization in academic writing. The qualitative phenomenology method was used in this study to dig deeper into students’ lived experiences that they interpreted while using Quillbot. The result based on the data analysis showed some lived experiences that the students interpreted such as Quillbot’s benefits and students’ future use of Quillbot, students’ perceptions of autonomy and assistance, students’ ethical consideration when utilizing Quillbot, and students’ adoption of Quillbot’s suggestion. The results of this study also emphasized students' awareness that Quillbot is a supporting tool that cannot replace their writing skills. This study provides valuable insight into how students interact with Quillbot, how it influences their writing process, and broadens the perspective of teachers, lecturers, instructors, and the wider community who often consider AI to have negative impacts on students’ learning process.